Tooth biomarkers to characterize the temporal dynamics of the fetal and early-life exposome. (December 2021) - Yu, Miao; Tu, Peijun; Dolios, Georgia; Dassanayake, Priyanthi S.; Volk, Heather; Newschaffer, Craig; Fallin, M. Daniele; Croen, Lisa; Lyall, Kristen; Schmidt, Rebecca; Hertz-Piccioto, Irva; Austin, Christine; et al.
Graphical abstract: Highlights: Tooth dentin extracts were profiled with untargeted chemical analysis. 390 metabolites and exogenous exposures were annotated in tooth extracts. Over 250 metabolite features discriminated the prenatal and postnatal tooth fractions. Unique metabolite features were found in the prenatal tooth fraction. Tooth exposome provides retrospective measurements of fetal and early life exposures. Abstract: Background: Teeth have unique histology that make this biomatrix a time-capsule for retrospective exposure analysis of fetal and early life. However, most analytic methods require pulverizing the whole tooth, which eliminates exposure timing information. Further, the range of chemicals and endogenous exposures that can be measured in teeth has yet to be fully characterized. Methods: We performed untargeted metabolomics on micro-dissected layers from naturally shed deciduous teeth. Using four liquid-chromatography high-resolution mass spectrometry analytical modes, we profiled small molecules (<1000 Da) from prenatal and postnatal tooth fractions. In addition, we employed linear regression on the tooth fraction pairs from 31 children to identify metabolites that discriminate between prenatal and postnatal exposures. Results: Of over 10, 000 features measured in teeth dentin, 390 unique compounds were annotated from 62 chemical classes. The class with the largest number of compounds was carboxylic acids and their derivatives (36%). Of the annotated exogenous metabolites (phthalates, parabens, perfluoroalkyl compounds, and cotinine) and endogenous metabolites (fatty acids, steroids, carnitines, amino acids, and others), 91 are linked to 256 health conditions through published literature. Differential analysis revealed 267 metabolites significantly different between the prenatal and the postnatal tooth fractions (adj. p-value < 0.05, Bonferroni correction), and 21 metabolites exclusive to the prenatal fraction. Conclusions: The prenatal and early postnatal exposome revealed from dental biomarkers represents a broad range of endogenous and exogenous metabolites for a comprehensive characterization in environmental health research. Most importantly, this technology provides a direct window into fetal exposures that is not possible by maternal biomarkers. Indeed, we identified several metabolites exclusively in the prenatal fraction, suggesting unique fetal exposures that are markedly different to postnatal exposures. Expansion of databases that include tooth matrix metabolites will strengthen biological interpretation and shed light on exposures during gestation and early life that may be causally linked with later health conditions.